Lockdown policy and its impact on employee termination and restaurant sustainability in Indonesia and European countries - Nurianna Thoha; Burhanudin Burhanudin; Marko Sebira Hermawan; Levi Fernanda Aditya (President University, 2022)
This research investigates employee termination decisions and the impact on restaurants’ sustainability during the COVID-19 pandemic. Restaurants in Indonesia, Germany, and the Netherlands have been affected by the lockdown policy that led to job cuts and termination of restaurants’ employees in those three counties. Therefore, the restaurant owners must cope with the lockdown situation in their country and find the best strategy to survive. This research is qualitative research that was conducted by using in depth semi-structured interviews to collect data from twelve interviewees who are working in three restaurants in Indonesia, and one restaurant each in Germany and the Netherlands. Due to the distance and the pandemic, most of the interviews were conducted online. All restaurants in this research are included in the casual restaurant category. This research found several factors of the termination process of the restaurant employees were included in the employee performance and employee enforcement factors. This research also discovered a relationship between the dismissal process and the sustainability of the restaurants during the COVID-19 pandemic that varied greatly among the three countries: Indonesia, Germany, and the Netherlands. The factors that influenced the restaurants’ sustainability included restaurant profit, government regulations, and the ways the restaurants’ owners or management navigated the pandemic effects. The results of this study will be useful to provide insight for businesses in the field of food and beverages, especially for restaurants during the COVID-19 pandemic.